1998
DOI: 10.1200/jco.1998.16.6.2060
|View full text |Cite
|
Sign up to set email alerts
|

Activity of fludarabine in previously treated Waldenström's macroglobulinemia: a report of 71 cases. Groupe Coopératif Macroglobulinémie.

Abstract: The responses rate in this population with a poor prognosis is close to that reported in shorter series. Patients with WM who are resistant to alkylating agents should be identified early, so that salvage therapy with nucleoside analogs can be started without delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…Alkylating agents and then purine analogues, initially used as single-agent treatments, gave an ORR between 50 and 75%, and 40 and 80%, respectively [13][14][15][16]. However, few patients entered complete remission, responses were short-lived, and progression-free survival was poor.…”
Section: Discussionmentioning
confidence: 99%
“…Alkylating agents and then purine analogues, initially used as single-agent treatments, gave an ORR between 50 and 75%, and 40 and 80%, respectively [13][14][15][16]. However, few patients entered complete remission, responses were short-lived, and progression-free survival was poor.…”
Section: Discussionmentioning
confidence: 99%
“…8 In small preliminary studies, promising clinical activity of both FAMP and 2-CDA in WM was observed. [8][9][10][11][12][13][14][15] In 1992, the Southwest Oncology Group (SWOG) began a prospective clinical trial to examine the natural history of WM and evaluate the clinical activity of FAMP in untreated patients as well as those who had previously undergone alkylating agent-based therapy. We present the results of this first large intergroup clinical trial in patients with WM.…”
Section: Introductionmentioning
confidence: 99%
“…Purine analogs may yield higher response rates when used as first-line therapy. [3][4][5] The combination of FDR with cyclophosphamide (Cy) gives an 80% response rate in untreated indolent malignancies such as CLL 6,7 and a 30% response rate in previously treated patients. 8 Recently, the German CLL group reported a better response rate and response duration in patients treated with FDR plus Cy than in those treated with FDR alone in a randomized phase III study.…”
mentioning
confidence: 99%